Sustainable theatre theory, context, practice - Taxopoulou, Iphigenia
"The book documents a sector in transition and presents theatre professionals, practitioners and organizations with a synthesis of information, knowledge and expertise to guide them to their own endorsement of sustainable thinking and practice. It is illustrated with inspiring case studies and interviews, from London's National Theatre, to Sydney Theatre Company, to the Göteborg Opera and the American Repertory Theatre. These foreground the work of pioneering institutions and individual practitioners whose artistic ingenuity, creative activism and sense of public mission have given shape, content and purpose to what we can now call 'sustainable theatre'.